THEMATIC PROGRESSION ON A NEWS TEXT ENTITLED “HEALTH MINISTRY ENSURES NO DATA LEAK IN PEDULILINDUNGI APP” FROM THE JAKARTA POST - Nike Puspita Wanodyatama Pasaribu (Universitas Widyatama, 2023)
This study aims to find out which theme is mostly used in the news text entitled “Health Ministry Ensures No Data Leak in PeduliLindungi App” and identify the kinds of patterns of thematic progression used in the news text. The method used for this study is descriptive qualitative. This study uses Paltridge (2012) thematic progression and Halliday (1985) theme and rheme as grounded theory. The result of the study showed that the most used theme from the news text is textual theme and the pattern of thematic progression used for this news text is multiple themes or split rheme. The result for the kind of theme used by the news text is considered from the number of times textual theme used in the news text which is about 23 times or 57.5%. The pattern of thematic progression used by the news text is multiple theme or split rheme because there are a mix of constant theme and linear theme on the overall pattern of the news text. Based on the pattern of thematic progression the number of constant themes used in the news text is 10 times and linear theme is three times, which makes it considered as a multiple theme or split rheme.